2018
DOI: 10.1002/joa3.12035
|View full text |Cite
|
Sign up to set email alerts
|

Portable out‐of‐hospital electrocardiography: A review of current technologies

Abstract: BackgroundAvailability of portable and home‐based electrocardiography (ECG) is an important medical innovation, which has a potential to transform medical care. We performed this review to understand the current state of out‐of‐hospital portable ECG technologies with respect to their scope, ease of use, data transmission capabilities, and diagnostic accuracy.MethodsWe conducted PubMed and Internet searches for “handheld” or “wearable” or “patch” electrocardiography devices to enlist available technologies. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
108
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 31 publications
0
108
0
3
Order By: Relevance
“…[10] Furthermore, the application of the devices relies on aggressive acrylic-based adhesives and exposes the patients to potential tissues damages during the removal process-key disadvantage that restricts the use of technology for neonate or young children who have fragile skin conditions. Consequently, there is a high demand for a cardiac monitoring solution that provides not only the acquisition of clinical-grade ECG, but also the form factor non-disruptive to everyday tasks as well as the real-time, continuous analysis of the patient's ECG for both improved diagnosis and timely intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Furthermore, the application of the devices relies on aggressive acrylic-based adhesives and exposes the patients to potential tissues damages during the removal process-key disadvantage that restricts the use of technology for neonate or young children who have fragile skin conditions. Consequently, there is a high demand for a cardiac monitoring solution that provides not only the acquisition of clinical-grade ECG, but also the form factor non-disruptive to everyday tasks as well as the real-time, continuous analysis of the patient's ECG for both improved diagnosis and timely intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of devices use a single lead, normally analogous to lead I. They do this by providing two electrodes to capture electrical signals from the fingers, thumb, wrist, or palm of each hand [33]. One of the best known is the AliveCor.…”
Section: Wearable Technologiesmentioning
confidence: 99%
“…The presence of an enhanced filter provides a much smoother tracing. Studies also suggest that even elderly patients found the device easy to use and that it did not restrict activities or cause anxiety [16,33,36]. It has been shown to be more likely to diagnose a symptomatic underlying rhythm than an HM [37].…”
Section: Wearable Technologiesmentioning
confidence: 99%
“…In their 2018 review, Banshal and Joshi identified 15 widely available personal ECG devices, but only six that were associated with Pubmed-listed studies. [11] Three of these are currently intended for prescription by medical professionals and three are available to individual consumers online. Table 1 shows representative prices for the commercially available devices, with the addition of the Apple Series 4 Watch (not included in the 2018 review as it had not been released).…”
Section: Personal Ecg Devicesmentioning
confidence: 99%